PENERAPAN STRATEGI PEMBELAJARAN MULTIPLE INTELLIGENCES DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS III DI MADRASAH IBTIDAIYAH AL-MUNAWWARAH KOTA JAMBI - A A Musyaffa; Yuniarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
Learning Interest of Class III Students in Thematic Learning at Madrasah Ibtidayah Al-Munawwarah Jambi City. This research focuses on the thematic learning process using multiple intelligences learning strategies. This study uses a classroom action research approach. Data collection techniques through interviews, observation, and documentation. Data analysis used descriptive analysis.In planning the teacher makes lesson plans, syllabus and prota and promissory notes according to existing provisions. The implementation of thematic learning is carried out in two cycles. Each cycle consists of two meetings and an evaluation of learning using the 2013 curriculum assessment with three aspects or domains assessed, namely knowledge, attitudes and skills. At the beginning of the observation, the researchers found that students' interest in learning was still low. Because teachers still use conventional methods (lecture methods) and have not used appropriate learning strategies. This makes students feel bored with the learning process in class. After implementing the learning process in cycle I and cycle II using multiple intelligences learning strategies, the learning interest of class III students has increased significantly. In the pre-cycle, the fifth grade students' interest in learning was 2.7% out of 15 students in the less interested category. With the number of students 1 is not interested, 6 students are not interested, 4 students are quite interested, and 4 students are in the interest category. And after the first cycle of action, the student's interest in learning scores rose to 3.1% from 15 students in the moderately interested category. With the number of students 8 students are quite interested, 7 students are interested. And it increased very significantly when the second cycle was carried out with a score of 4.2% of 15 students in the category approaching very interest. With 2 students with sufficient interest, 13 students in the interest category. The increase in students' interest in learning can also be seen from the cognitive and psychomotor aspects. Thus, it can be concluded that the use of multiple intelligences learning strategies can increase students' interest in learning thematic learning at Madrasah Ibtidaiyah Al-Munawwarah Jambi City